Smooth muscle cell phenotypic switching in atherosclerosis - Gomez, Delphine (Oxford University Press, 2012)
Smooth muscle cells (SMCs) possess remarkable phenotypic plasticity that allows rapid adaptation to fluctuating environmental cues, including during development and progression of vascular diseases such as atherosclerosis. Although much is known regarding factors and mechanisms that control SMC phenotypic plasticity in cultured cells, our knowledge of the mechanisms controlling SMC phenotypic switching in vivo is far from complete. Indeed, the lack of definitive SMC lineage-tracing studies in the context of atherosclerosis, and difficulties in identifying phenotypically modulated SMCs within lesions that have down-regulated typical SMC marker genes, and/or activated expression of markers of alternative cell types including macrophages, raise major questions regarding the contributions of SMCs at all stages of atherogenesis. The goal of this review is to rigorously evaluate the current state of our knowledge regarding possible phenotypes exhibited by SMCs within atherosclerotic lesions and the factors and mechanisms that may control these phenotypic transitions.